GPS Signal Performance Testing Based on Material Variations Of Portable On-Demand (POD) And GPS Placement For Aerial Photography Missions - Kehi, De Richi; Hartini, Dwi; Mardwianta, Benedictus; Prattiwi, Elisabeth Anna; Santoso, Djarot Wahju (Vortex, 2025)
In aerial photography, the use of camera systems integrated with GPS signals is crucial for determining the position and velocity of an aircraft or drone. The Portable On-Demand (POD) serves as a payload container for equipment such as cameras, and the POD material can influence GPS signal quality. This study aims to evaluate the quality of received GPS signals and to assess the effect of camera distance on GPS performance. Experimental tests were conducted using three POD material types (original, E-glass, and carbon) and two GPS systems (Emlid Reach and Pixhawk). The results indicate that the E-glass POD provides the best performance, achieving signal-to-noise ratio (SNR) values above 45 dB and a PDOP value of 1.7. Additionally, the E-glass POD detected up to 34 satellites at a camera distance of 0 cm. In contrast, the original and carbon PODs exhibited inferior performance, including occurrences of a “No Solution” status. Therefore, the E-glass POD is more reliable in maintaining GPS signal quality and positioning accuracy for aerial photography missions.